Concepções e status da leitura em inglês em cursos universitários em Maceió: cursos do setor terciário : análise de sistemas e secretariado executivo. - Coutinho, Tânia Maria Marques (2008)
The aim of this work was to investigate the treatment given to reading in classes of English as a foreign language at colleges in Maceió, especially in two courses of the tertiary sector of economy Systems Analysis Courses and Executive Secretariat Course. The relevance of the work is related to the importance of reading in English as a necessary activity to the academic and professional literacy. From this research it was possible to observe reading conceptions and its status in force nowadays in the institutions studied. In order to investigate that issue, the methodology used was based on the observations of classes in four colleges in which the discipline Inglês Instrumental (English for Specific Purposes) is taught. Thus, this work can be considered as being a qualitative research, of an ethnographic kind. Besides classroom observations, field note taking, informal interviews and questionnaires for both students and teachers were also used. The theoretical background was based on the studies of the history of reading, the socio-cognitive and discoursive aspects of reading strategies, foreign language teaching approaches and principles of English for Specific Purposes. One of the results obtained indicated that, in a general way, the teachers observed included some of the English for Specific Purposes assumptions in their classes in spite of demonstrating strong influences of the traditional features of language teaching.